How adult attachment style influence marital communication patterns: a review of literature - Deylami, Neda; Hassan, Siti Aishah (IDOSI Publications, 2014)
This study attempts highlight theories and research about adult attachment styles and communication patterns. The aim of this study is to explain and try to show the effect of adult attachment style on marital communication patterns to better understanding dynamics of emotional bonding is created primarily I childhood and continue in thorough out of life. Attachment was originally a conceptualization of the emotional bond between a caregiver and child and then grew to become an organizing framework for understanding adult romantic relationships. Based on the numerical studies and research, if this emotional bond shape is positive and secure, it can make a deep and effective relationship between persons and important others. The result of review literature has shown there is a direct relationship between the style of attachment and satisfied relationship. Researchers have indicated that individuals with secure attachment styles express higher levels of marital satisfaction than those couples who have insecure attachment styles, as well as more constructive communication and emotional regulation. Furthermore, the literature review indicated that couples who reporting low levels of conflict benefited more mutual constructive communication compare those couple with high levels of conflict. The findings of this study can be implicated for couple and family therapists. Definitely, higher functioning marriages create healthier environments for children and families.